Limitation of use and abuse of the authority of the discretion which create the state financial losses - Achmad Muzammil,; Basuki Rekso Wibowo,; Slamet Suhartono, (Technium Social Sciences Journal, 2020)
Discretion is the authority of government administration to face problems for which there are no regulations (eemten in het recht), and/or (vage norms) so that it requires explanation, interpretation, consideration of various related interests, and/ or because there are options that can be made in regulation. By government organs in carrying out their duties, namely discretionary authority. The limits on the use of discretionary powers must not deviate from and conflict with the rules above, in accordance with the hierarchy of laws and regulations, not violating human rights and obligations of citizens, not being used arbitrarily, still in the position of the scope of the basic regulations, used in a state of coercion/urgent for the sake of public welfare/interest, and based on the General Principles of Good Governance. Responsibility of Public Officials uses discretionary powers which results in detournement de pouvair with wederrechtelijkheid which results in losses to state finances.